2020
DOI: 10.1037/pas0000950
|View full text |Cite
|
Sign up to set email alerts
|

The Multidimensional Self-Control Scale (MSCS): Development and validation.

Abstract: Trait self-control is important for well-being and mental and physical health. Most extant measures of self-control are limited in that they do not account for the multidimensionality and specificity of the trait. The aim of this study was to develop and validate a multidimensional and hierarchical scale of self-control in a full and a short version. The development of the Multidimensional Self-Control Scale (MSCS) and the Brief Multidimensional Self-Control Scale (BMSCS) was based on focus groups, a pilot, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 99 publications
(168 reference statements)
1
24
0
Order By: Relevance
“…They thereby buttress recent findings and theorizing on the complex processes underlying high TSC individuals' achievements (e.g., Duckworth et al, 2016;Fujita, 2011;Gillebaart & de Ridder, 2015;Hofmann & Kotabe, 2012;Katzir et al, 2021;Nilsen et al, 2020).…”
Section: Theoretical Contributionssupporting
confidence: 74%
See 1 more Smart Citation
“…They thereby buttress recent findings and theorizing on the complex processes underlying high TSC individuals' achievements (e.g., Duckworth et al, 2016;Fujita, 2011;Gillebaart & de Ridder, 2015;Hofmann & Kotabe, 2012;Katzir et al, 2021;Nilsen et al, 2020).…”
Section: Theoretical Contributionssupporting
confidence: 74%
“…A recent neuroimaging study found evidence that TSC was associated with some indicators of sustained and successful negative emotion down-regulation (Paschke et al, 2016). These insights are also reflected in current developments in the measurement of trait self-control which integrate multiple strategies and dimensions relating to mental control beyond behavioral inhibition and impulse control (e.g., reappraisal; attentional control; Katzir et al, 2021;Nilsen et al, 2020). Importantly, the ability for emotion-regulation seems to tie in with a sense that one is able to do so (Gross & John, 2003).…”
Section: Self-control and Moralization Of Mental Statesmentioning
confidence: 90%
“…Second, although the Brief Self-Control Scale (BSCS) provides information on students’ overall self-control capacity, it does not explicitly inform us which aspects of self-control can be related to psychological health and life satisfaction (Lindner et al, 2015 ). A solution to this limitation is to adopt validated scale supporting the multi-faceted, multidimensional nature of self-control (Nilsen et al, 2020 ). Third, the number of samples collected via convenience sampling method from the university students was not large enough, and there was major unequal distribution of male and female subjects, thus findings from the present study may not be generalizable to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Let us return to the two-factor model in Figure 5 with severely non-normal marginals. Although not the recommended approach (Foldnes & Grønneberg, 2021b), cont-ML is still in wide use in empirical research (e.g., Marsh et al, 2013; Nilsen et al, 2020). This method estimates Pearson correlations directly on integer-encoded data.…”
Section: Factor Analysis For Ordinal Datamentioning
confidence: 99%